STRATEGI KEBERHASILAN USAHA HOME INDUSTRY AYU BAKERY DI KECAMATAN KOLAKA - Riana Andayani; Moh Abd Azis (Jurnal Ekonomi Bisnis Syariah, 2020)
Home Industry is a place to live that doubles as a business, both offices, trade in goods and services. Home Industry plays an important role for the economic growth of the community, one of which is the Ayu Bakery Home Industry which is located at Jalan. Andi Jemma, Kolaka sub-district, but in terms of marketing it is not yet comprehensive. The formulation of the problem in this study is how the success strategy of Ayu Bakery's Home Industry Business in Kolaka District and the inhibiting factors of Ayu Bakery's Home Industry Strategy. The purpose of this study was to determine the Success Strategy of Ayu Bakery's Home Industry Business in Kolaka District and the inhibiting factors of Ayu Bakery's Home Industry Strategy. The research method used includes the type of qualitative research, which is the object of the Ayu Bakery Home Industry Business Success Strategy in Kolaka District. Data collection techniques include interviews, documentation and observation. And the research instrument used is an interview guide to the owner, employee, distributor, and consumer of Ayu Bakery as well as documentation in the form of interview sheets and documentation photos. The results of this research are that the Ayu Bakery Home Industry Business Success Strategy in Kolaka District is to increase production capacity to meet market demand, maintain the quality of raw materials, maintain good relations with distributors by providing guarantees and feed back for consumers and distributors in terms of taste, size , and packaging, create a healthy competitiveness, and innovative product development and maintain prices.